2019
DOI: 10.4252/wjsc.v11.i7.375
|View full text |Cite
|
Sign up to set email alerts
|

Predicting differentiation potential of human pluripotent stem cells: Possibilities and challenges

Abstract: The capability of human pluripotent stem cell (hPSC) lines to propagate indefinitely and differentiate into derivatives of three embryonic germ layers makes these cells be powerful tools for basic scientific research and promising agents for translational medicine. However, variations in differentiation tendency and efficiency as well as pluripotency maintenance necessitate the selection of hPSC lines for the intended applications to save time and cost. To screen the qualified cell lines and exclude problemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Next, we analyzed the pluripotent differentiation potential of GPC4sh hiPSCs in vitro and in vivo by performing embryoid body (EB)‐mediated spontaneous differentiation and teratoma formation assays, respectively 29 . By using immunocytochemistry, we found that differentiating GPC4sh EBs exhibit loss of the hiPSC marker OCT4 and express markers of the three germ layers, such as OTX2 for Neuroectoderm, BRA for Mesoderm and SOX17 for Endoderm, similar to controls (Figures 1K and S2I).…”
Section: Resultsmentioning
confidence: 82%
“…Next, we analyzed the pluripotent differentiation potential of GPC4sh hiPSCs in vitro and in vivo by performing embryoid body (EB)‐mediated spontaneous differentiation and teratoma formation assays, respectively 29 . By using immunocytochemistry, we found that differentiating GPC4sh EBs exhibit loss of the hiPSC marker OCT4 and express markers of the three germ layers, such as OTX2 for Neuroectoderm, BRA for Mesoderm and SOX17 for Endoderm, similar to controls (Figures 1K and S2I).…”
Section: Resultsmentioning
confidence: 82%
“…Additionally, there is a risk of debilitating or life-threatening side-effects, such as tumorigenesis -due to remaining proliferating cells -as well as graft-induced dyskinesias (GIDs) of unknown origin, previously observed in some patients with fetal transplants 2,4 . The differentiation and malignancy potential of a given iPSC line remains difficult to predict 17 , and pretransplantation quality assessment at later time points can be expected to reveal more pertinent information regarding the in-vivo outcome. Mature neurons however have an overly complex and fragile architecture, and thus are poorly tolerant to pre-transplantational handling procedures, particularly enzymatic dissociation 4,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Directed differentiation, on the contrary, might test very specific pathways, and the optimal assay to use is still under discussion (The International Stem Cell Initiative, 2018). For a predictive assay, most probably directed differentiation into the cell type of interest is the most meaningful readout (Liu et al, 2019).…”
Section: Of 26mentioning
confidence: 99%